2022
DOI: 10.1038/s41598-022-17646-6
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometrics versus DNA barcoding for the identification of malaria vectors Anopheles dirus and An. baimaii in the Thai-Cambodia border

Abstract: Anopheles (Cellia) dirus Peyton & Harrison and Anopheles baimaii Sallum & Peyton are sibling species within the Dirus complex belonging to the Leucosphyrus group, and have been incriminated as primary vectors of malaria in Thailand. In the present study, DNA barcoding and geometric morphometrics were used to distinguish between An. dirus and An. baimaii in the international border areas, Trat Province, eastern Thailand. Our results revealed that DNA barcoding based on the cytochrome c oxidase subunit I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Recently, DNA barcoding was applied to aid mosquito identification in Thailand and found that although this technique has high efficiency, some mosquitoes are unable to identify the exact species, such as Anopheles dirus and An. baimaii [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, DNA barcoding was applied to aid mosquito identification in Thailand and found that although this technique has high efficiency, some mosquitoes are unable to identify the exact species, such as Anopheles dirus and An. baimaii [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen landmarks on the wing vein structure of the Lutzia mosquitoes were identified and digitized for the GM analyses ( Figure 3 ). This study’s landmark placements are based on earlier research that successfully identified certain mosquito species [ 23 , 24 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…dirus COI exhibit low interspecific differences [ 63 , 64 ]. Chaiphongpachara et al [ 65 ] recently used DNA barcoding to separate An . dirus and An .…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is limited by the need for complete morphological specimens and practitioner expertise [ 10 ]. Currently, effective alternative methods for species identification include geometric morphometrics and DNA barcoding; both may support the standard method to accurately identify mosquito samples that are morphologically similar [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%